Parallel Manipulation and Flexible Assembly of Micro-Spiral via Optoelectronic Tweezers - Liang, Shuzhang; Sun, Jiayu; Zhang, Chaonan; Zhu, Zixi; Dai, Yuguo; Gan, Chunyuan; Cai, Jun; Chen, Huawei; Feng, Lin (Frontiers in Bioengineering and Biotechnology, 2022)
Micro-spiral has a wide range of applications in smart materials, such as drug delivery, deformable materials, and micro-scale electronic devices by utilizing the manipulation of electric fields, magnetic fields, and flow fields. However, it is incredibly challenging to achieve a massively parallel manipulation of the micro-spiral to form a particular microstructure in these conventional methods. Here, a simple method is reported for assembling micro-spiral into various microstructure via optoelectronic tweezers (OET), which can accurately manipulate micro/bio-particles by projecting light patterns. The manipulation force of micro-spiral is analyzed and simulated firstly by the finite element simulation. When the micro-spiral lies on the bottom of the microfluidic chip, it can be translated or rotated towards the target position by applying control forces simultaneously at multiple locations on the long axis of the micro-spiral. Through the OET manipulation, the length of the micro-spiral chain can reach 806.45μm. Moreover, the different parallel manipulation modes are achieved by utilizing multiple light spots. The results show that the micro-spirulina can be manipulated by a real-time local light pattern and be flexibly assembled into design microstructures by OET, such as a T-shape circuit, link lever, and micro-coil pairs of devices. This assembly method using OET has promising potential in fabricating innovative materials and microdevices for practical engineering applications.